2008
DOI: 10.1021/jf7036856
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Transmission to Segureño Lamb Meat from Ewesʼ Diet Supplemented with the Distillate from Rosemary (Rosmarinus officinalis) Leaves

Abstract: The aim of the present work is to study whether the introduction of rosemary plant byproduct, from plant steam distillation, in daily Segurena sheep feeding allows the transfer of active antioxidant components to lamb meat, without detriment to the animal productivity. For this, 36 Segurena ewes were assigned randomly to three homogeneous groups. One group was fed a basal diet as a control and the diet of the other two groups was modified by substituting 10 or 20% of the control diet (respectively) with distil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 27 publications
8
100
2
2
Order By: Relevance
“…Antioxidant status of meat and liver samples Although in the present study the use of naringin did not seem to significantly affect the antioxidant status of the meat, previous studies carried out on finishing cows and lambs showed an improvement in this parameter when plant extracts rich in polyphenols were included in the diet (Moñ ino et al, 2008;Gobert et al, 2010;Luciano et al, 2011). This effect was related to the presence of polyphenols in muscle (Luciano et al, 2011).…”
Section: Discussioncontrasting
confidence: 61%
“…Antioxidant status of meat and liver samples Although in the present study the use of naringin did not seem to significantly affect the antioxidant status of the meat, previous studies carried out on finishing cows and lambs showed an improvement in this parameter when plant extracts rich in polyphenols were included in the diet (Moñ ino et al, 2008;Gobert et al, 2010;Luciano et al, 2011). This effect was related to the presence of polyphenols in muscle (Luciano et al, 2011).…”
Section: Discussioncontrasting
confidence: 61%
“…Nieto (2009) reported that rosemarybased and thymus-based diets decreased the levels of hexanal, heptanal, octanal, nonanal, 1-penten-3-ol, pentanol, 1-octen-3-ol and heptanol, inhibiting lamb rancidity during the storage in similar conditions to those used in our study. In this study, ewes were given high quantities (10% to 20%) of distilled rosemary leaf, a source of carnosic acid and carnosol (Moñino et al, 2008), which resulted in a reduction in the level of hexanal and of other quantitatively minor VOCs in lamb meat from day 7 onwards. These results were explained in a further study by the lesser degradation of linoleic and linolenic acids protected by phenolic antioxidants (Nieto et al, 2012).…”
Section: Inhibiting Rancid Volatiles In Lamb With Dietary Diterpenesmentioning
confidence: 99%
“…The use of by-products as natural antioxidants is a way to replace synthetic antioxidants, such as wastes from industrial residues of olive oil (Lesagemeessen et al, 2001), essential oil of rosemary (Moñ ino et al, 2008;Nieto et al, 2010b) and grapes (Torres and Bobet, 2001). Thymus zygis ssp.…”
Section: Introductionmentioning
confidence: 99%